Growth Slowdowns and the Middle-Income Trap - Aiyar, Shekhar (International Monetary Fund, 2013)
The "middle-income trap" is the phenomenon of hitherto rapidly growing economies stagnating at middle-income levels and failing to graduate into the ranks of high-income countries. In this study we examine the middle-income trap as a special case of growth slowdowns, which are identified as large sudden and sustained deviations from the growth path predicted by a basic conditional convergence framework. We then examine their determinants by means of probit regressions, looking into the role of institutions, demography, infrastructure, the macroeconomic environment, output structure and trade structure. Two variants of Bayesian Model Averaging are used as robustness checks. The results-including some that indeed speak to the special status of middle-income countries-are then used to derive policy implications, with a particular focus on Asian economies